Research gaps identified in Iran's health technology assessment reports - Farideh Mohtasham; Bahareh Yazdizadeh; Mohammadreza Mobinizadeh (BMC, 2023)
Abstract Introduction Identifying gaps in the evidence is a useful byproduct of conducting a health technology assessment (HTA). This study aims to identify research gaps in Iran's HTA reports. Method We reviewed the HTA reports published between 2014 and 2016. Then, we developed two separate questionnaires for principal investigators (PIs) and independent HTA researchers. The questionnaire for independent HTA researchers consisted of four main parts. However, the PIs' questionnaire consisted of two main parts. We also conducted a literature search in the PubMed database in November 2017 to find frameworks for prioritizing research gaps. We also conducted a semi-structured interview with the head of the Iran's HTA Office at that time and sought feedback based on his expert opinion about questionnaires, the priority-setting tool and our process for extracting research gaps. Results A total of 11 HTA reports published between 2014 and 2016 by Iran's HTA Office were selected for the study. Of these 11 reports, 5 involved technologies related to medical equipment, while 6 involved medical and surgical interventions. Assessing the outcomes of technology use in various indications and updating HTAs when new evidence arises; evaluating the viewpoints of patients, clinicians and key technology users; conducting post-marketing evaluations of technology; comparing the impact of the technology in question to other treatments for the same condition; and requesting long-term clinical and cost-effectiveness data for technologies with limited follow-up periods were identified as the main gaps by independent HTA researchers and PIs. Conclusions The research gaps identified from Iran's HTAs could be utilized by research funding agencies.